Usborne Great Britain quiz book - Smith, Sam; Primo Ramón (Usborne Publishing London, 2017)
Usborne Great Britain Quiz Book is an entertaining and educational activity book designed to engage young readers with fun facts and challenging questions about Great Britain. Covering a wide range of topics, including history, geography, culture, and landmarks, the book invites children to test their knowledge and learn new information in an interactive way. Each quiz is presented with colorful illustrations and accessible language, making it suitable for kids of various ages. The book not only encourages learning but also promotes curiosity about the rich heritage and diversity of Great Britain, making it a delightful addition to any young reader's collection.